Improving job performance through strengthening the organizational culture and interpersonal communication - Widodo Sunaryo; Nancy Yusnita; Mustofa Mustofa (Jurnal Konseling dan Pendidikan, 2020)
The teacher’s job performance is one of the important factor that influence the process of achieving educational goals. Maintaining and increasing teacher’s job performance become urgent and important parts in educational processes. When we found in certain district that the teachers’ job performance were in low level condition, we realized that we need to study the problem and to find out the way to improve teacher’s job performance. This study designed as a quantitative research used sample of 200 teachers derived by random sampling from its population, and used questionnaires as instruments to collect research data. The Correlational and SITOREM Analysis used to analyze the data. The research had generated findings that the school Organizational Culture and teacher’s Interpersonal Communication as partially and simultaneously had strong significant correlations with job performance. It had been found also that some dimensions of school Organizational Culture and teacher’s Interpersonal Communication were recommended as high-level priority to be strengthened in order to improve teacher’s job performance.